Change in Santri's Entrepreneurial Mindset Through the Salafi Model Quality Management System in Indonesia Pesantren - Abdul Bashith; Muh. Yunus; Abdul Malik Karim Amrullah; Ahmad Muhtadi Ridwan; Ramadhani Lausi Mkumbachi; Saiful Amin; Waluyo Satrio Adji (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
This study aimed to (1) identify entrepreneurial product that is feasible to be developed to support the pesantren’s independence, (2) find the appropriate assistance strategies to improve the pesantren’s entrepreneurship through the salafi model quality management system (SMQMS), and (3) describe the performance of Islamic entrepreneurship after applying SMQMS. The method used is participatory action research with the stages of plan, action, observe, and reflect. This study selected a sample of 64 students, 4 teachers, and kyai (pesantren leaders), using a purposive sampling technique. The participants all attended Islamic vocational high school in Darus Sholawat Pesantren, Madiun, Indonesia. Descriptive analysis were performed to analyze the data. The results of the study indicate that: (1) entrepreneurial product that is deserved to be prioritized to develop is sharia laundry business, because involves its impact on the pesantren’s learning process and economy; (2) the strategy for developing the pesantren’s educational quality is the use of SMQMS; (3) the independence of the pesantren is shown in the learning aspect through the